GAMBARAN MEKANISME KOPING MAHASISWA DALAM MENYUSUN SKRIPSI DI PROGRAM STUDI ILMU KEPERAWATAN STIKES HANG TUAH PEKANBARU - Waiez Lavari Lavari; Susi Erianti; Tengku Abdur Rasyid (STIKes Al-Insyirah Pekanbaru, 2019)
ABSTRACT In the process of writing a Thesis, the students usually have problems and obstacles which impede them to finish it. The way of facing the problem is different depends on the mechanism of coping with the thesis. The research was aimed to find out the mechanism of students in coping with the thesis. It was a quantitative research with descriptive design. The participants were 62 people which were chosen by total sampling technique. The research used questionnaire with 20 questions. The data was analyzed by using univariate analysis. The result showed 64,5 % of female respondents with 22,03 years old in average and 56,5 % respondents used mal-adaptive mechanism of coping . It showed 62,8 % was the female students and 37,2 % was male at Nursing Program Study of STIKes Hang Tuah Pekanbaru. The result recommended the Program Study especially the lecturers to help the students who are writing the thesis by giving motivation and counseling so that the students can finish the thesis well and on time. Keywords: Coping Mechanism, Student, Thesis